2020
DOI: 10.3390/cells9020431
|View full text |Cite
|
Sign up to set email alerts
|

The Phenotype and Functional Activity of Mesenchymal Stromal Cells in Pediatric Patients with Non-Malignant Hematological Diseases

Abstract: As the biology of mesenchymal stromal cells (MSCs) in patients with non-malignant hematological diseases (NMHD) is poorly understood, in the current study we performed a basic characterization of the phenotype and functional activity of NMHD-MSCs. Bone marrow (BM) of patients with thalassemia major (TM) possessed a significantly higher number of nucleated cells (BM-MNCs)/mL BM than healthy donors (P < 0.0001), which however did not result in a higher number of colony forming units-fibroblast (CFU-F) per mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
1
1
0
Order By: Relevance
“…Microscopical analysis demonstrated that CFU-Fs exhibited intra- and interdonor heterogeneity in both SCD and NS groups, with either large or small colonies formed by fibroblastoid cells ( Figure 1(e) ). These findings indicate an effective enrichment of CFU-F in BM-MNC samples from patients with osteonecrosis, which is consistent with previous reports [ 8 , 35 ].…”
Section: Resultssupporting
confidence: 93%
“…Microscopical analysis demonstrated that CFU-Fs exhibited intra- and interdonor heterogeneity in both SCD and NS groups, with either large or small colonies formed by fibroblastoid cells ( Figure 1(e) ). These findings indicate an effective enrichment of CFU-F in BM-MNC samples from patients with osteonecrosis, which is consistent with previous reports [ 8 , 35 ].…”
Section: Resultssupporting
confidence: 93%
“…These studies include both preclinical and clinical trials of either autologous or allogeneic MSCs. Infusion of MSCs has been performed to evaluate their safety and therapeutic efficacy in diseases of the immune[ 3 ], hematological[ 4 ], cardiovascular[ 5 , 6 ], nervous[ 7 , 8 ], respiratory[ 9 ], digestive[ 10 ], skeletal[ 11 ], endocrine[ 12 ], and reproductive[ 13 ] systems[ 14 ]. To date, more than 1000 MSC-based clinical trials have been registered in the United States National Institute of Health database[ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%